Onset of breeding among Swedish Starlings Sturnus vulgaris in relation to spring temperature in 1981—2003 - Svensson, Sören (Ornis Svecica, 2004)
Both spring temperature and date of the first Starling Sturnus vulgaris egg were highly correlated between different study sites and weather stations in the southern half of Sweden. In southern Sweden, but not in northern Sweden, onset of breeding correlated strongly with spring temperature, particularly during the last ten days of April, the period that happens to coincide with the start of breeding. The response was one to two days per degree. No response was found with periods relative to the start of egg-laying, indicating that in the latter part of April the general conditions for breeding are normally satisfied as soon as temperature reaches a certain level. Possible climatic trends were too weak to be detected in the noise of the annual fluctuations. The best current estimate of long-term spring temperature increase during the next one hundred years is four degrees, which would mean that the Starling will start egg-laying 4–8 days earlier at the end of the present than at the end of the previous century.